Recycling of Pineapple (Ananas comosus) Leaf Agro-waste as One of the Raw Materials for Production of Eco-friendly New Paper. Issue 1 (December 2020) - Teo, Pao Ter; Zakaria, Siti Koriah; Azhar Taib, Mustaffa Ali; Budiman, Faisal; Mohamed, Mazlan; Yusoff, Abdul Hafidz; Ahmad Sobri, Sharizal
Abstract: This project aimed to recycle pineapple (Ananas comosus) leaf agro-waste and wastepaper into new paper using simple processing routes that involve pulping, mixing, sieving, compaction and drying. Subsequently, physical and mechanical properties, as well as the morphology of the pineapple leaf fiber (PALF)-based paper were investigated accordingly. Two different samples were prepared whereby the first sample is pineapple leaf fiber mixed with wastepaper, and another sample is pure pineapple leaf fiber paper. The samples were tested for tensile properties by using the universal testing machine, morphological analysis using scanning electron microscopy, and density measurement using a densitometer. It was found that the sample consist of pineapple leaf and wastepaper shows a higher tensile strength than the sample containing only PALF. Moreover, the density of paper with pineapple leaf fiber and wastepaper mix was higher than the paper with only pineapple leaf fiber. In the future, further modification of body formulation is necessary to further improve the properties of the pineapple leaf fiber-based paper.